Plasticity-Related PKMζ Signaling in the Insular Cortex Is Involved in the Modulation of Neuropathic Pain after Nerve Injury - Jeongsoo Han; Minjee Kwon; Myeounghoon Cha; Motomasa Tanioka; Seong-Karp Hong; Sun Joon Bai; Bae Hwan Lee (Neural Plasticity)
The insular cortex (IC) is associated with important functions linked with pain and emotions. According to recent reports, neural plasticity in the brain including the IC can be induced by nerve injury and may contribute to chronic pain. Continuous active kinase, protein kinase Mζ (PKMζ), has been known to maintain the long-term potentiation. This study was conducted to determine the role of PKMζ in the IC, which may be involved in the modulation of neuropathic pain. Mechanical allodynia test and immunohistochemistry (IHC) of zif268, an activity-dependent transcription factor required for neuronal plasticity, were performed after nerve injury. After ζ-pseudosubstrate inhibitory peptide (ZIP, a selective inhibitor of PKMζ) injection, mechanical allodynia test and immunoblotting of PKMζ, phospho-PKMζ (p-PKMζ), and GluR1 and GluR2 were observed. IHC demonstrated that zif268 expression significantly increased in the IC after nerve injury. Mechanical allodynia was significantly decreased by ZIP microinjection into the IC. The analgesic effect lasted for 12 hours. Moreover, the levels of GluR1, GluR2, and p-PKMζ were decreased after ZIP microinjection. These results suggest that peripheral nerve injury induces neural plasticity related to PKMζ and that ZIP has potential applications for relieving chronic pain.